2000
DOI: 10.1262/jrd.46.207
|View full text |Cite
|
Sign up to set email alerts
|

The Microvasculature of the Ovary. A Review by SEM of Vascular Corrosion Casts.

Abstract: Abstract. The vascular changes of the ovary were studied by scanning electron microscopy of vascular corrosion casts in estrous, pseudopregnant (stimulated with human chorionic gonadotropin -hCG) and pregnant rabbits. The results demonstrated that ovarian cycle and pregnancy may induce both structural and functional changes in the ovarian vessels. In fact the ovarian blood vessels adapted their structure to the temporary functional needs of the recruited follicles or corpora lutea. These changes involved both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 46 publications
4
23
1
1
Order By: Relevance
“…Additionally, scanning electron microscopy studies of ovarian follicle corrosion casts of various animals revealed similar observations [5,[13][14][15][16][17]. Thus, these findings support the concept that follicular atresia is accompanied by significant thecal capillary structural changes [18].…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, scanning electron microscopy studies of ovarian follicle corrosion casts of various animals revealed similar observations [5,[13][14][15][16][17]. Thus, these findings support the concept that follicular atresia is accompanied by significant thecal capillary structural changes [18].…”
Section: Discussionsupporting
confidence: 76%
“…This close anatomical relationship was described previously in other species, such as guinea-pigs 9 , rats 13 , rabbits 11,18 , mice 6 , primates such as Rhesus monkeys 8 and, baboons 21 .…”
Section: Discussionsupporting
confidence: 82%
“…However, in guinea pigs, the arteria ovarica originated either from the aorta at about the level of origin of the arteria renalis, direct branches of arteria renalis, or common trunks with arteria renalis and in some cases formed anastomoses with branches of the arteria renalis 9 . In rabbits, it arose from the aorta abdominalis, immediately behind the origin of the inferior mesenteric artery 3 , whereas it left the abdominal aorta slightly caudal to the arteria renalis in mice 6 , New Zealand rabbits 11 and in rats 2,23 . Each of the ovarian arteries after emerging from the aorta abdominalis, divided into 2 branches, the caudal branches served the Fallopian tubes and uterine horns, and the cranial branch mainly supplied blood to the ovary in guinea pigs 4,8,9 , rats 4,8 , mice 6 and in New Zealand rabbits 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian follicles of living animals have been known to be dynamic structures that undergo a gradual increase in volume during the various phases preceding ovulation, and the follicular development is always accompanied by significant structural changes of perifollicular capillary networks (Macchiarelli 2000). The perifollicular capillary networks are initially formed when the membrana granulosa of secondary follicles has developed into a multilayered follicle cell population.…”
Section: Introductionmentioning
confidence: 99%
“…The perifollicular capillary networks are initially formed when the membrana granulosa of secondary follicles has developed into a multilayered follicle cell population. Furthermore, they also develop a single-layered to multilayered thick theca interna, as the secondary follicles grow up to larger or mature Graafian follicles (Kanzaki et al 1982, Kitai et al 1985, Kranzfelder & Maurer-Schultze 1989, Yamada et al 1994, Macchiarelli 2000, Jiang et al 2002. These morphological changes of the follicular microvasculature have shown an urgent need for increased blood supply and nutritional support systems during the follicular development and oocyte maturation.…”
Section: Introductionmentioning
confidence: 99%